Isolation and functional characterization of 5-enolpyruvylshikimate 3-phosphate synthase gene from glyphosate-tolerant Pseudomonas nitroreducens strains FY43 and FY47 - Tan, Xue Li; Othman, Rofina Yasmin; Teo, Chee How (Springer Verlag (Germany), 2020)
5-Enolpyruvylshikimate 3-phosphate synthase (EPSPS) is the primary target for the broad-spectrum herbicide, glyphosate. Improvement of EPSPS gene for high level of glyphosate tolerance is important to generate glyphosate-tolerant crops. In this study, we report the isolation and characterization of EPSPS genes of glyphosate-tolerant Pseudomonas nitroreducens strains FY43 and FY47. Both P. nitroreducens strains FY43 and FY47, which showed glyphosate tolerance up to 8.768% (518.4 mM, 32 × higher than field application), were isolated from soil samples collected from oil palm plantation with a long history of glyphosate application. The glyphosate tolerance property of EPSPS genes of strains FY43 and FY47 was functionally characterized by expressing the genes in Escherichia coli strain BL21(DE3). Error-prone PCR was performed to mutagenize native EPSPS gene of strains FY43 and FY47. Ten mutagenized EPSPS with amino acid changes (R21C, N265S, A329T, P71L, T258A, L184F, G292C, G292S, L35F and A242V) were generated through error-prone PCR. Both native and mutated EPSPS genes of strains FY43 and FY47 were introduced into Escherichia coli strain BL21(DE3) and transformants were selected on basal salt medium supplemented with 8.768% (518.4 mM) glyphosate. Mutants with mutations (R21C, N265S, A329T, P71L, T258A, L35F, A242V, L184F and G292C) showed sensitivity to 8.768% glyphosate, whereas glyphosate tolerance for mutant with G292S mutation was not affected by the mutation. © 2020, King Abdulaziz City for Science and Technology.